2022
DOI: 10.1186/s12866-022-02605-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of endophytic fungal community in Huperzia serrata from different ecological areas and their correlation with Hup A content

Abstract: Background Huperzine A (Hup A) has attracted considerable attention as an effective therapeutic candidate drug used to treat Alzheimer’s disease. Whereas, the production of Hup A from wild plants faced a major challenge, which is the wild Huperzia Serrata harbor a low Hup A content, has a long-life cycle, and has a small yield. At present, several reports showed that Hup A is produced by various endophytic fungal strains isolated from H. serrata, thereby providing an alternative method to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
2
5
1
Order By: Relevance
“…However, in February and May, the endophytic fungal communities of leaf were similar to that of stem. This was consistent with the reported results [ 38 40 ]. The NMDS analysis of the same tissue across four months revealed that there were significant differences in the communities of root and leaf, but the analysis of stem communities provided a poor representation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, in February and May, the endophytic fungal communities of leaf were similar to that of stem. This was consistent with the reported results [ 38 40 ]. The NMDS analysis of the same tissue across four months revealed that there were significant differences in the communities of root and leaf, but the analysis of stem communities provided a poor representation.…”
Section: Discussionsupporting
confidence: 94%
“…The highest richness and diversity of endophytic fungal community was in stems, followed by leaves and roots. This result is different from previous reports [ 38 40 ], which may be due to the fact that endophytic fungi were identified from H. serrata in different seasons, and the differences of endophytic communities in tissues are shaped by the factors such as plant species, soil type, geographic, and environmental conditions [ 41 ]. NMDS analysis showed that there were significant differences between endophytic fungal communities when all four seasons were considered in root, stem and leaf.…”
Section: Discussioncontrasting
confidence: 92%
“…At the genus level, Pseudomonas, Sphingomonas, Methylobacterium, and Hymenobacter were also found to be relatively abundant in leaves of both cultivated (Hallmann et al, 1997;Rosenblueth and Martínez-Romero, 2006;Miliute et al, 2015;Afzal et al, 2019;Christian et al, 2021) and non-cultivated plants (Ding and Melcher, 2016;Afzal et al, 2019). On the other hand, the majority of leaf endophytic fungi in Heuchera belonged to Ascomycota and Basidiomycota, similarly reported as two of the most dominant fungal endophyte classes in its close relative, Saxifraga (Zhang and Yao, 2015) and across a variety of host plants (Zimmerman and Vitousek, 2012;Jin et al, 2013;Fan et al, 2020;Pang et al, 2022). In addition, Penicillium, Pleosporaceae, Alternaria, and Colletotrichum have also been documented as predominant fungal endophytes associated with leaves of multiple host plant species Araújo et al, 2001;Gamboa and Bayman, 2001;Romero et al, 2001;Douanla-Meli et al, 2013;Jin et al, 2013;Matsumura and Fukuda, 2013;Fang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The temporal dynamics of microbial communities, including root-related microbiomes, are influenced by many factors, such as soil pH, nitrogen, and phosphorus content (Edwards et al, 2015 ). Many studies have shown a high correlation between the accumulation of secondary metabolites in medicinal plant soil fungal communities and the rhizosphere, such as P. ginseng (Wei et al, 2020 ), Glycyrrhiza uralensis (Liu et al, 2023 ); Glehnia littoralis (Liu et al, 2023 ); and endophytic fungal communities, such as licorice (He et al, 2019 ; Dang et al, 2021 ), Rheum palmatum (Chen et al, 2021 ), Sophora alopecuroides (Ju et al, 2022 ), and Huperzia serrata (Pang et al, 2022 ). In this study, HTS was carried out to estimate the composition and diversity of endophytic fungal and rhizosphere soil fungal communities in F. dibotrys and elucidate the role of fungal communities in secondary metabolites in F. dibotrys .…”
Section: Discussionmentioning
confidence: 99%